(untitled) (Islamic Sciences Journal, 2023)
Objectives: 1- Demonstrate the evolution of writing in the Science of Counting Verses 2- trace the literature in verse counting, and classification of each book into its relevant phase. 3- Classifying writing phases, in terms of time span and content. Methodology: The methodology adopted is inductive, analytical, and historical methods. Main Results: 1- The books of the science of counting verses gradually added verse counters, ultimately mentioning them all. 2- The demonstration of oldest books within this science, showing the historic order and degree of inclusiveness of all topics part of the Science of Counting 3- The importance of only writing on the history of sciences following the examination of diverse writings within a science, in terms of time and methodology. Recommendations: - To highlight a need to reassess the critical reproduction of some books on verse counting, in consideration to the impulsiveness of some authors during reproduction. - To attract much attention to this science, especially among Quran reciters.